An efficient generalized minimized residual simulation technique for continuation power flow studies - Jasni, Jasronita; Azis, Norhafiz; Hizam, Hashim; Ab Kadir, Mohd Zainal Abidin; Mariun, Norman; Mohd Noor, Samsul Bahari; Sobri, Shafreeza (Knowledgia Review, Malaysia, 2008)
This study has been initiated to improve the time taken by the CPF method and eliminate the convergence problem for the tested system by enforcing the General Minimal Residual (GMRES) method at the initial point at the start up, herewith referred as CPF-GMRES solver. Analyses have shown that this new algorithm not only reduced the computation time but also eliminated the convergence problem for the tested system.